1994
DOI: 10.1007/bf00926043
|View full text |Cite
|
Sign up to set email alerts
|

Role of Δ9 desaturase activity in the maintenance of high levels of monoenoic fatty acids in hepatoma cultured cells

Abstract: The incorporation and delta 9 desaturation of exogenous [14C]stearic acid were studied in HTC 7288c cells in suspension. We examined the uptake of the acid over a wide range of concentrations (0-160 microM) after incubating the cells for 6 h in a chemically-defined medium. Under this experimental condition, the uptake of the labeled acid was more extensive than that obtained from static cultures or from monolayer of isolated hepatocytes of rats. At an external concentration of 160 microM ca. 52 nmoles of acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…de Alaniz and Marra (1994) also demonstrated significant contribution of the stearoyl-CoA desaturase system to the high levels of oleic acid present in this kind of hepatoma cells. Peroxisome proliferators comprise a diverse group of chemicals which are regarded as rodent hepatocarcinogens and/or liver tumor promoters (Palut, 1997).…”
Section: Influence Of Liver Cancer On Fatty Acid Metabolismmentioning
confidence: 73%
“…de Alaniz and Marra (1994) also demonstrated significant contribution of the stearoyl-CoA desaturase system to the high levels of oleic acid present in this kind of hepatoma cells. Peroxisome proliferators comprise a diverse group of chemicals which are regarded as rodent hepatocarcinogens and/or liver tumor promoters (Palut, 1997).…”
Section: Influence Of Liver Cancer On Fatty Acid Metabolismmentioning
confidence: 73%
“…In addition, the increased in MUFA, specifically C18:1x9 and C18:2x6 is associated with the disruption of the delta-6 desaturase enzyme known to be inhibited by FB 1 [30]. The resultant increase in MUFA could also be due to an increase in delta-9 desaturase as observed in tumour growth in mouse mammary carcinoma cells [70], hepatoma cells [71], human leukemia and lymphoma cells [72]. The growth of mammary carcinogenesis in vitro was blocked by the addition of an inhibitor of delta-9 desaturase [73].…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have suggested a link between ⌬9-d activity and tumor growth. Thus, high levels of MUFAs are required by mouse mammary carcinoma cells (18), hepatoma cells (33), and human leukemia and lymphoma cells (34). In all of these cases, the required MUFA levels are assured by overexpression of the genes encoding ⌬9-d. Inhibition of ⌬9-d and, consequently, of oleic acid biosynthesis blocks the growth of transplanted mammary tumor in rats (19).…”
Section: Discussionmentioning
confidence: 99%